EFEKTIVITAS BERKAS MLAKU DEWE TERHADAP PELAYANAN PUBLIK DI KECAMATAN SUKODONO KABUPATEN SIDOARJO - Nona Vita Rahayu; Hendra Sukmana (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to analyze and describe the effectiveness of the Mlaku Dewe file for public services in Sukodono District, Sidoarjo Regency. In this study, researchers used a type of descriptive qualitative method by implementing an approach in the form of observation and interviews. The data used in this study comes from primary data and secondary data. In this study, the researchers selected informants who were related to the object under study, including the sub-district head, administrative and general affairs staff in Sukodono District. The theory used in this study is the theory according to Richard M. Steers (1980: 1). In this theory there are three indicators that are used consisting of indicators of achievement of objectives, indicators of integration, indicators of adaptation. The research results found in the first indicator, an indicator of achieving goals, of course, in achieving goals, it is necessary to have stages and their periodization, while the researchers divided them into five years of achieving the goals of using the Mlaku Dewe Files. The second indicator is the integration indicator, it was found that the socialization of the service program using the File Mlaku Dewe application system had been carried out properly. The last indicator is an adaptation indicator. As for the results, it was found that administrative and general affairs staff in the Sukodono sub-district always use the File Mlaku Dewe application in carrying out administrative services to the community.AbstrakPenelitian ini bertujuan menganalisa dan mendeskripsikan efektivitas Berkas Mlaku Dewe terhadap pelayanan publik di Kecamatan Sukodono Kabupaten Sidoarjo.. Dalam penelitian ini peneliti menggunakan jenis metode kualitatif deskriptif dengan melaksanakan sebuah pendekatan berupa observasi dan wawancara. Adapun data yang dipergunakan pada penelitian ini berasal dari data primer serta data sekunder. Pada penelitian ini peneliti memilih informan yang berhubungan dengan objek yang diteliti antara lain Camat, Staff urusan tata usaha dan umum di Kecamatan Sukodono. Adapun teori yang dipergunakan dalam penelitian ini adalah teori menurut Richard M. Steers (1980: 1). Pada teori ini terdapat tiga indikator yang digunakan terdiri dari indikator Pencapaian Tujuan, indikator Integrasi, indikator Adaptasi. Pada hasil penelitian didapati pada indikator pertama, indikator pencapaian tujuan tentunya didalam sebuah pencapaian tujuan diperlukan adanya tahapan-tahapan serta periodesasinya adapun peneliti membagi kedalam lima tahun pencapaian tujuan penggunaan Berkas Mlaku Dewe. Indikator kedua adalah indikator integrasi didapati bahwa sosialisasi program pelayanan dengan menggunakan sistem aplikasi Berkas Mlaku Dewe telah dilaksanakan dengan baik. Indikator terakhir adalah indikator adaptasi adapun hasil yang didapati bahwa para staff urusan tata usaha dan umum yang terdapat di kecamatan Sukodono selalu menggunakan aplikasi Berkas Mlaku Dewe dalam melakukan pelayanan administrasi kepada masyarakat.